2012
DOI: 10.4269/ajtmh.2012.11-0475
|View full text |Cite
|
Sign up to set email alerts
|

Virological Surveillance of Dengue in Saint Martin and Saint Barthélemy, French West Indies, Using Blood Samples on Filter Paper

Abstract: * RT-PCR = reverse transcriptase-polymerase chain reaction. † Laboratory-confirmed dengue cases based on positive NS1 or/and IgM patients reported by the laboratories. DENGUE VIROLOGICAL SURVEILLANCE USING FILTER PAPERfor DENV-1 (336 of 352), 4.3% for DENV-2 (15 of 352), and 0.3% for DENV-4 (1 of 352) ( Table 3 ).The first epidemic reported in Saint Barthélemy began at the end of October 2008 (Week 43), within 3 weeks after the dengue epidemic alert was issued for Saint Martin ( Table 3 and Figure 2 ). The bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…26 The present study has confirmed these observations in a regional Pacific setting and shown that serum initially collected for routine viral serology can be substituted for whole blood. Moreover, using an appropriate extraction protocol it was demonstrated that FPdried serum or blood samples can provide DENV RNA in a quantity and a quality that allows sequencing of the full E gene and DENV genotype identification.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…26 The present study has confirmed these observations in a regional Pacific setting and shown that serum initially collected for routine viral serology can be substituted for whole blood. Moreover, using an appropriate extraction protocol it was demonstrated that FPdried serum or blood samples can provide DENV RNA in a quantity and a quality that allows sequencing of the full E gene and DENV genotype identification.…”
Section: Discussionsupporting
confidence: 90%
“…23 More recently, FP-dried whole blood spots have been employed for the molecular diagnosis of DENV. [24][25][26] We have evaluated whole blood/serum dried on FPcards and transported by standard mail, at ambient temperatures, for use in DENV diagnosis and surveillance in a Pacific setting.…”
Section: Objectivesmentioning
confidence: 99%
“…Dengue serology performed on DBS is clearly suitable for seroprevalence studies, although it is less clear for the diagnosis of acute primary and acute secondary infections. Dengue serotyping is epidemiologically important and can also be successfully performed from DBS 43,139…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] and Matheus et al . [ 20 ] reported detection of dengue virus by RT-PCR from dried blood spots on filter paper. The former study tested dengue 2 and dengue 3 viruses from FP from 52 patients and the latter tested FP from 666 NS1 positive patients.…”
Section: Discussionmentioning
confidence: 99%